Understanding patients’ experience living with diabetes type 2 and effective disease management: a qualitative study following a mobile health intervention in Bangladesh - Yasmin, Farzana; Ali, L.; Banu, Bilkis; Rasul, Fatema; Sauerborn, Rainer; Souares-Coutant, Aurélia (BMC health services research, 2020)
In 2017, 425 million adults worldwide had diabetes; 80% were living in low and middle-income countries. Bangladesh had 6.9 million adults with diabetes; death from diabetes comprised 3% of the country’s total mortality. This study looked at different factors (personal, familial, social, and financial) affecting both the life of patients with diabetes type 2 and the management of the disease. It also explored patient’s perception of the mobile health intervention in the context of disease management and helped to explain the findings obtained from the quantitative part of this study.
Gesehen am 26.03.2020